2018
DOI: 10.1002/esp.4306
|View full text |Cite
|
Sign up to set email alerts
|

Which way do you lean? Using slope aspect variations to understand Critical Zone processes and feedbacks

Abstract: Soil‐mantled pole‐facing hillslopes on Earth tend to be steeper, wetter, and have more vegetation cover compared with adjacent equator‐facing hillslopes. These and other slope aspect controls are often the consequence of feedbacks among hydrologic, ecologic, pedogenic, and geomorphic processes triggered by spatial variations in mean annual insolation. In this paper we review the state of knowledge on slope aspect controls of Critical Zone (CZ) processes using the latitudinal and elevational dependence of topog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
93
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(114 citation statements)
references
References 183 publications
(281 reference statements)
7
93
3
Order By: Relevance
“…Now, geophysicists travel among CZOs to image the subsurface with a battery of instruments to image the belowground landscape (St. Clair et al, 2015). In another example, after the Boulder Creek CZO began emphasizing slope aspect as a useful natural experiment to examine controls on CZ architecture and function in 2009, similar analyses at other CZOs led to highlighted linkages among aspect, water, biota, regolith structure, and episodic events (West et al, 2014;Ebel et al, 2015;Pelletier et al, 2017). Finally, a deep drilling project ("drill the ridge") was proposed and then pursued at many CZOs, and these data in turn led to a special issue describing regolith formation (Riebe et al, 2016).…”
Section: The Nine Emergent Roles Of Czosmentioning
confidence: 99%
See 1 more Smart Citation
“…Now, geophysicists travel among CZOs to image the subsurface with a battery of instruments to image the belowground landscape (St. Clair et al, 2015). In another example, after the Boulder Creek CZO began emphasizing slope aspect as a useful natural experiment to examine controls on CZ architecture and function in 2009, similar analyses at other CZOs led to highlighted linkages among aspect, water, biota, regolith structure, and episodic events (West et al, 2014;Ebel et al, 2015;Pelletier et al, 2017). Finally, a deep drilling project ("drill the ridge") was proposed and then pursued at many CZOs, and these data in turn led to a special issue describing regolith formation (Riebe et al, 2016).…”
Section: The Nine Emergent Roles Of Czosmentioning
confidence: 99%
“…A full elucidation of hypotheses is beyond the scope of this paper and only a subset is shown in Table 4. Many have been published in collaborative papers (Rempe and Dietrich, 2014;Riebe et al, 2016;Li et al, 2017;Pelletier et al, 2017;Yan et al, 2017;Brantley et al, 2017a). Here we summarize three multidisciplinary discoveries that have large implications for the prediction of flow paths relevant to the largest supply of accessible and drinkable water available to humans -water contained in rock and regolith (Fetter, 2001;Banks et al, 2009).…”
Section: The Nine Emergent Roles Of Czosmentioning
confidence: 99%
“…Recent studies conducted in Arctic regions—using high‐resolution geophysical and remote sensing data—have revealed that microtopography could produce significant spatial heterogeneity in soil moisture and plant community distributions at several‐meter or submeter scales (S. S. Hubbard et al, ; Dafflon et al, ; H. M. Wainwright et al, ). While the slope aspect of the hillslopes can be considered as a first‐order large‐scale control (Pelletier et al, ; Yetemen et al, ), the controlling factors within each hillslope have not yet to the authors' knowledge been investigated. Given that soil moisture is very sensitive to microtopography, it could be an important factor governing the spatial organization of the ecosystem in a water‐limited region.…”
Section: Introductionmentioning
confidence: 99%
“…Given their inherently complex topography, microclimates vary at short distances (10s of meters), as both air and soil temperatures have been documented to differ on north versus south aspects in California range improvement studies (Evans, Kay, & Young, 1975;Raguse & Evans, 1977). Moreover, differences in microclimate (including soil climate) across complex topography have been recognized as a force affecting ecohydrology and vegetation, which convey their effects on landscape evolution, for example, the steepening of north-facing slopes in the northern hemisphere midlatitudes (Poulos, Pierce, Flores, & Benner, 2012;Yetemen, Istanbulluoglu, Flores-Cervantes, Vivoni, & Bras, 2015;Pelletier et al, 2018). These differences extend into the soil mantle, affecting soil temperature, soil moisture, and plant growth.…”
mentioning
confidence: 99%